Сучасні технології розширеної реальності: аналіз та етапи створення AR-масок - Булага, А. В. (ХНУРЕ, 2024)
In today's digital world, reality and virtual space are greatly benefited by augmented reality (AR) technologies. One of the most popular forms of AR is AR-masks, which recreate the appearance of the average person using virtual elements. AR-masks are visual effects that can be added to the exposure or additional middle nature of a person under the influence of various mobile add-ons or social measures. These masks can include a variety of graphic elements, animations, filters and 3D models that are superimposed on real objects through the camera of a smartphone or other device.
Keywords: технології розширеної реальності; створення AR-масок